(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses qualitative and quantitative changes in modern Uzbek philosophy of history, some features of new philosophical thinking in our national spirituality. Innovative technologies and their positive impact on the development of our spirituality were discussed.